Holistic higher-order thinking in solving environmental problems: A profile of Indonesian undergraduate students - M. Mualimin; Rahmania Pamungkas (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Holistic higher-order thinking (H-HOT) is needed by someone who lives in the 21st century to solve environmental problems. This study aims to determine the ability of H-HOT to solve environmental problems in undergraduate students of biology and biology education programs in Indonesia. The research used a survey method. The sample was taken using a purposive sampling technique, namely only undergraduate students from the biology and biology education program who had graduated from environmental theme lectures. The research instrument in the form of a H-HOT ability test in solving environmental problems is 10 numbers that have been validated by material and construction experts, and empirically validated given to 205 respondents online. Data in the form of H-HOT ability values ​​in solving environmental problems were analyzed descriptively and quantitatively. The results showed that the ability of H-HOT to solve environmental problems in undergraduate students of the biology study program obtained an average score of 24.81, biology education study program is 27.48, and overall average score of all undergraduate students from both the Biology study program and the Biology Education study program are 26.23. The conclusion of this study is that the ability of H-HOT in solving environmental problems in undergraduate students of biology and biology education programs is in a very low category so that efforts need to be made to improve. The study implies a need for improved educational approaches to enhance students' higher-order thinking skills for effectively solving environmental problems.